Biopolymer-Nanocomposite Hybrid Materials as Potential Strategy to Remove Pesticides in Water: Occurrence and Perspectives - Baigorria, Estefanía [UNESP]; Fraceto, Leonardo F. [UNESP] (Wiley, 2022)
During the last three decades, the use of pesticides to increase agricultural yields has grown exponentially and excessively. These agricultural practices, in conjunction with various natural factors, have led to the contamination of water bodies. Preserving contamination-free hydrographic basins is a challenge and a priority of the community. This article first presents a classification of the various pesticides, the existing regulations concerning their use, and their influence on the aquatic environment. Several methodologies for the removal of pesticides from aqueous media are presented, with emphasis on adsorption techniques. In addition, a discussion is provided for materials with nanoscale characteristics as promising adsorbents of pesticides present in water. A focus on research regarding nanostructured hybrid biopolymeric materials is proposed, with critical appraisal and future perspectives. Factors such as the ability to recover, regenerate, and reuse these hybrids, together with their environmentally friendly characteristics, make them highly attractive options for the proposed purpose. However, their current application in the treatment of pesticide-contaminated water remains low. This new generation of biopolymeric nanocomposite hybrid materials emerges as a viable, cost-effective, and eco-friendly option for use in the provision of safe water to society.